Analysis of the LNAPL Migration Process in the Vadose Zone under Two Different Media Conditions - Rui Zuo (MDPI AG, 2021)
This study focused on the processes of free infiltration, precipitation displacement, and natural attenuation of the LNAPL under the condition of near-surface leakage. Sandbox experiments were performed to explore the migration characteristics of LNAPL in the vadose zone with two media structures and the influences of the soil interface on the migration of LNAPL. The results indicate that the vertical migration velocity of the LNAPL infiltration front in medium and coarse sand was 1 order of magnitude higher than that in fine sand and that the LNAPL accumulated at the coarse–fine interface, which acted as the capillary barrier. Displacement of precipitation for LNAPL had little relationship with rainfall intensity and was obviously affected by medium particle size, where coarse sand (40.78%) > medium sand (20.5%) > fine sand (10%). The natural attenuation rate of the LNAPL in the vadose zone was related to the water content of the media; the natural attenuation rate of fine sand was higher. This study simulated the process of the LNAPL leakage from the near surface into the layered heterogeneous stratum, improved the understanding of the migration of the LNAPL under different stratum conditions, and can provide support for the treatment of LNAPL leakage events in the actual site.